Sosialisasi Penggunan Media Video Animasi dalam Pembelajaran Guru SD Inpres 12/79 Watampone - Hafid, Abd.; rosmalah, Rosmalah; Dh, Satriani; Hafid, Hardianti (SMART: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service activity is to enhance the pedagogical competence of teachers at SD Inpres 12/79 Biru 1 through the use of animated video media in teaching. This activity involved teachers from SD Inpres 12/79 Biru 1 as participants in a socialization session conducted by the Community Service Team. The session covered the concept of animated video media, steps for its implementation in the classroom, and examples of how it can be used in elementary school subjects. During the session, participants were provided with a guidebook on how to use animated video media, enabling them to gain a clear understanding and be inspired to apply it in their own teaching. The results of the activity received positive feedback, as participants gained knowledge on how to use animated video media, which can help improve their pedagogical skills, particularly in designing and utilizing media that aligns with learning objectives. This ultimately motivates students, increases their interest and engagement, and improves academic achievement. The conclusion of this activity is that participants gained practical knowledge about animated video media that can be used to motivate students, enhance their interest, and improve learning outcomes.AbstrakTujuan kegiatan pengabdian masyarakat ini adalah untuk meningkatkan kompetensi pedagogik guru di SD Inpres 12/79 Biru 1 menggunakan media video animasi dalam pembelajaran, kegiatan ini melibatkan guru-guru SD Inpres 12/79 Biru 1 sebagai peserta sosialiasasi yang dilaksanakan oleh tim Pengabdian Kepada Masyarakat. Sosialisasi ini mencakup pemahaman konsep media video animasi, langkah-langkah penggunaan dalam pembelajaran, dan penayangan contoh penggunaan media animasi dalam pembelajaran mata Pelajaran di Sekolah Dasar. Selama sosialisasi, peserta diberikan file pedoman penggunaan media video animasi, sehingga peserta memperoleh pemahaman dan dapat menginspirasi untuk menggunakannya dalam pembelajaran. Hasil kegiatan mendapat respon positif memperoleh pengetahuan penggunaan media video animasi karena dapat membantu meningkatkan kemampuan pedagogik mereka yaitu merancang dan menggunakan media video animasi sesuai tujuan pembelajaran di SD sehingga siswa dapat termotivasi, berminat, aktif, dan berprestasi. Kesimpulan kegiatan ini adalah peserta memperoleh ilmu pengetahuan praktis tentang media video animasi yang dapat digunakan dalam pembelajaran untuk memotivasi, meningkatkan minat, dan hasil belajar siswa.